THE INSTITUTION OF THE UNIVERSITY: THE CURRENT DISCOURSE ON THE EUROPEAN HIGHER EDUCATION AND RESEARCH SPACE - Kwiek, Marek (Antwerpen: Wolf Legal Publishers., 2006)
The institution of the university is playing a significant role in the processes of the emergence of the common European higher education and common European research spaces. What is clear, though, is that in neither of them, the university is seen in a traditional way we know from the debates preceding the advent of globalization, the speeding up of the process of the European integration and the passage from the industrial and service societies to the postindustrial, global, knowledge and information societies (see Kwiek 2000). The institution, in general, has already found it legitimate, useful and necessary to be evolving together with radical transformations of the social setting in which it functions. The new world we are approaching assumes different names in different formulations and the social, cultural, and economic processes in questions are debated in multiple vocabularies of social sciences. The present paper focuses on recent debates about common European higher education and research spaces. Their emergence will have far-reaching consequences for both EU-15, the enlarged Europe and other postcomunist transition countries. The ideas of both European spaces are evolving and are still not clearly defined. One thing is certain, though: we are confronting a major redesign of what research and teaching in European public sector are supposed to be, of how public higher education institutions, including universities, are supposed to function and be financed (at least from EU funds), and what roles students and faculty are increasingly pressed to assume in European higher education systems. At the moment, the European Higher Education Area is much more of a desired ideal to be achieved within the ongoing Bologna process, with very limited funding available for its implementation in particular countries; the ideal of the European Research Area (ERA), by contrast, has already determined the shape of the 6th Framework Programme of Research – the biggest source of EU research funds, totaling 17.5 billion EUR for 2002-2006.
Keywords: European Research Area; ERA; European Higher Education Area; EHEA; Bologna Process; Lisbon Strategy; European higher education; European universities; university reforms; transition economies; higher education policy; educational policy